Prototype Pengembangan Sistem Web Modul PAUD Berbasis ADDIE dengan Pendekatan Pedagogik - Claudia, Sindy; Magdalena, Hilyah (LPPM Universitas Mulia, 2025)
PAUD (Early Childhood Education) Mutiara Bunda is one of the educational institutions that has a very large role in the success of education. At PAUD Mutiara Bunda, currently it has not implemented a computerized sistem (manual), especially in making teaching modules so that it often takes a long time and costs a lot of money in printing and often loses the teaching module printout. Therefore, the researcher designed a prototype for developing a web-based teaching module using the Research and Development (R&D) method with the ADDIE Analysis, Design, Development, Implementation, Evaluation model in designing a web sistem prototype so as to produce a sistem that suits user needs. At the design stage, the researcher used the UML and Figma prototypes. The results of this study are a prototype of a web sistem for developing teaching modules that can make it easier for teachers to process teaching modules and can help parents see their children's learning activities.